Binding of human coronary artery endothelial cells to plasma‐treated titanium dioxide nanotubes of different diameters. Issue 5 (30th January 2016) - Flašker, Ajda; Kulkarni, Mukta; Mrak‐Poljšak, Katjuša; Junkar, Ita; Čučnik, Saša; Žigon, Polona; Mazare, Anca; Schmuki, Patrik; Iglič, Aleš; Sodin‐Semrl, Snezna
Abstract: Nanoscale topography in improving vascular response in vitro was established previously on various titanium surfaces. In the present study different surface nanotopographies that is different diameters of titanium dioxide (TiO2 ) nanotubes (NTs) were fabricated by electrochemical anodization and conditioned with highly reactive gaseous oxygen plasma. The morphology of different diameter NTs was studied by scanning electron microscopy and atomic force microscopy, while changes in chemical composition on the surface before and after plasma treatment were determined by X‐ray photoelectron spectroscopy. Performance of human coronary artery endothelial cells (HCAEC) on those conditioned surfaces was studied in regard to cell proliferation, released IL‐6 protein and immunofluorescence microscopy (IFM). We show that HCAEC function is dependent on the diameter of the TiO2 NTs, functioning far less optimally when bound to 100 nm TiO2 NTs as compared to Ti foil, 15 nm NTs or 50 nm NTs. There were improved, morphological cell shape changes, observed with IFM, between HCAEC growing on oxygen‐rich plasma‐treated versus nontreated 100 nm NTs. These endothelialized conditioned Ti nanosurfaces could elucidate optimization conditions necessary for vascular implants in coronary arteries. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1113–1120, 2016.